Untangling the importance of niche breadth and niche position as drivers of tree species abundance and occupancy across biogeographic regions. Issue 9 (22nd June 2020) - Vela Díaz, Dilys M.; Blundo, Cecilia; Cayola, Leslie; Fuentes, Alfredo F.; Malizia, Lucio R.; Myers, Jonathan A.
Abstract: Aim: Ecological niches shape species commonness and rarity, yet, the relative importance of different niche mechanisms within and across ecosystems remains unresolved. We tested the influence of niche breadth (range of environmental conditions where species occur) and niche position (marginality of a species' environmental distribution relative to the mean environmental conditions of a region) on tree‐species abundance and occupancy across three biogeographic regions. Location: Argentinian Andes; Bolivian Amazon; Missouri Ozarks. Time period: 2002–2010. Major taxa studied: Trees. Methods: We calculated abiotic‐niche breadths and abiotic‐niche positions using 16 climate, soil and topographic variables. For each region, we used model selection to test the relative influence of niche breadth and niche position on local abundance and occupancy in regional‐scale networks of 0.1‐ha forest plots. To account for species–environment associations caused by other mechanisms (e.g., dispersal), we used null models that randomized associations between species occurrences and environmental variables. Results: We found strong support for the niche‐position hypothesis. In all regions, species with higher local abundance and occupancy occurred in non‐marginal environments. Observed relationships between occupancy and niche position also differed from random species–environment associations in all regions. Surprisingly, we found little support for the niche‐breadth hypothesis. Observed relationships between both local abundance and niche breadth, and occupancy and niche breadth, did not differ from random species–environment associations. Main conclusion: Niche position was more important than niche breadth in shaping species commonness and rarity across temperate, sub‐tropical and tropical forests. In all forests, tree species with widespread geographic distributions were associated with environmental conditions commonly found throughout the region, suggesting that niche position has similar effects on species occupancy across contrasting biogeographic regions. Our findings imply that conservation efforts aimed at protecting populations of common and rare tree species should prioritize conservation of both common and rare habitats.